Access to justice in civil matters : a critical analysis of legal representation of minors under guardianship in Rwanda - Dowuona-Hammond, Christine (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.